Pirfenidone in restrictive allograft syndrome after lung transplantation: A case series. Issue 12 (17th August 2018) - Vos, Robin; Wuyts, Wim A.; Gheysens, Olivier; Goffin, Karolien E.; Schaevers, Veronique; Verleden, Stijn E.; Van Herck, Anke; Sacreas, Annelore; Heigl, Tobias; McDonough, John E.; Yserbyt, Jonas; Godinas, Laurent; et al.
Abstract : Pirfenidone may attenuate the decline of pulmonary function in restrictive allograft syndrome (RAS) after lung transplantation. We retrospectively assessed all lung transplant recipients with RAS who were treated with pirfenidone for at least 3 months (n = 11) in our lung transplant center and report on their long‐term outcomes following initiation of pirfenidone. Main outcome parameters included evolution of pulmonary function and overall survival. Pirfenidone appears to attenuate the decline in forced vital capacity and forced expiratory volume in 1 second. Notably, 3 patients were bridged to redo‐transplantation with pirfenidone for 11 (5‐12) months and are currently alive, while 3 other patients demonstrate long‐term stabilization of pulmonary function after 26.6 (range 18.4‐46.6) months of treatment. Median overall 3‐year survival after RAS diagnosis was 54.5%. Subjective intolerance, mainly anorexia and nausea, necessitating pirfenidone dose de‐escalation in 55% of patients, as well as calcineurin dose increase requirements with about 20% are important complications during pirfenidone treatment after lung transplantation. Our findings provide further evidence that pirfenidone appears to be safe and may attenuate the rate of decline in lung function in patients with RAS, but the actual clinical benefit cannot be assessed in the context of this study design and requires further investigation in a larger randomized trial. Abstract : This case series of lung transplant recipients treated with pirfenidone for restrictive allograft syndrome demonstrates that pirfenidone may attenuate the rate of pulmonary function decline.